2000
DOI: 10.1177/009365000027005003
|View full text |Cite
|
Sign up to set email alerts
|

Television Viewing, Fat Stereotyping, Body Shape Standards, and Eating Disorder Symptomatology in Grade School Children

Abstract: A survey of 303 first- to third-grade children measured relationships between (a) television viewing and interpersonal attraction (IA) to television characters and (b) fat stereotyping, body shape standards, and eating disorder symptomatology. Television viewing predicted an increased tendency among males to stereotype a fat female target and also predicted increased eating disorder symptomatology among participants of both genders. IA to thin television characters was not a consistent predictor of thinness-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
3
10

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 25 publications
9
111
3
10
Order By: Relevance
“…More recently, media have tremendous effects on people's live. Several studies have shown that girls and women who have higher levels of exposure to media imagery tend to be less satisfied with the way that they look than those with lower levels of exposure [12,[31][32][33] . Botta [34] found that magazine exposure (mediated by social comparison processes) was linked to body dissatisfaction in boys as well as girls and in 2003 argued that: magazine reading, social comparisons and critical body image processing are important predictors of body image and eating disturbances in adolescent boys and girls [35] .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, media have tremendous effects on people's live. Several studies have shown that girls and women who have higher levels of exposure to media imagery tend to be less satisfied with the way that they look than those with lower levels of exposure [12,[31][32][33] . Botta [34] found that magazine exposure (mediated by social comparison processes) was linked to body dissatisfaction in boys as well as girls and in 2003 argued that: magazine reading, social comparisons and critical body image processing are important predictors of body image and eating disturbances in adolescent boys and girls [35] .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, competitive weight loss reality programs have been shown to promote individual blame beliefs and contribute to weight stigma [6,44,49], and children exposed to greater amounts of media express greater stigmatization toward overweight individuals [11,21]. These stereotypes are internalized by some overweight individuals and can result in serious health consequences [47].…”
Section: Discussionmentioning
confidence: 99%
“…41 Some evidence supports the argument that viewing television is related to holding stereotypes about obese individuals. In a study of elementary school children, Harrison 42 found that the more television boys watched, the more likely they were to assign negative stereotypes to an overweight female. According to the second approach, not all images are equivalent, and audience members will orient themselves to characters they favor.…”
mentioning
confidence: 99%